Prospects for reducing social need in Uzbekistan - ugli, Bakhtiyorov Bobur Bakhodir (International Journal of Psychosocial Rehabilitation, 2020)
This paper makes analyses of the prospects for reducing social need in Uzbekistan. On this case, medium term of the prospects of the reduction of social need. Finally, theoretical and statistical analyses were concluded and pointed out both outcomes and shortcomings of the research